Use of ketamine for depression and suicidality in cancer and terminal patients: Review of current data - Aderonke Oyetunji; Christian Huelga; Kailee Bunte; Rachel Tao; Val Bellman (AIMS Press, 2023)
Depression and suicidality are significant challenges faced by cancer patients, particularly those in advanced stages of the disease or nearing the end of life. Conventional antidepressant therapies often have limited effectiveness or delayed onset of action, making the exploration of alternative treatments crucial. The use of ketamine as a potential treatment for depression and suicidality in cancer and terminal patients has gained considerable attention in recent years. This review article aims to provide a comprehensive analysis of the current data regarding the efficacy and safety of ketamine in this specific population. This review presents an overview of clinical trials and case studies investigating the use of ketamine in this population. It explores the effectiveness of ketamine as a standalone treatment or in combination with other interventions. Furthermore, the article addresses the limitations and future directions of research in this field. It highlights the need for larger, well-controlled studies with long-term follow-up to establish the efficacy, safety and optimal treatment parameters of ketamine for depression and suicidality in palliative care.